Lifestyle Interventions in Weight Loss Programs for Community- Based Patients with Severe Mental Disorders: A Scoping Review - Picardo, Giulia; Donnoli, Clara; Liotta, Giuseppe (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Patients with psychiatric disorders face exacerbated physical health issues and reduced life expectancy, primarily due to premature cardiovascular diseases. The intricate relationship between lifestyle factors, illness, and psychotropic medications contributes to this phenomenon. The focus of this research is to evaluate weight management interventions for individuals with Severe Mental Disorders through a comprehensive scoping review, investigating the characteristics, types, modalities and topics of interventions to provide a useful tool for professionals who want to promote lifestyle interventions for people with Severe Mental Disorders.Methods. Eligible articles were peer-reviewed studies that reported an intervention targeted to patients with Severe Mental Disorders and aimed at promoting health through nonpharmacological interventions (including but not limited to nutritional education, physical activity and exercise interventions).Results. A total of 20 studies with a total of 3,886 participants were evaluated.The studies included patients with a weighted mean age of 44.37 (SD=4.72) and a mean Body Mass Index of 34.7 kg/m2 (SD=3.56). Varied interventions, mostly conducted in the US, showed promising weight reduction and cardiovascular risk management results among patients with psychiatric disorders. However, disparate methods used in the studies hindered the evaluation of outcomes. The studies, which yielded the most interesting results, included parallel cluster randomized controlled trials, which showed improvements in HDL cholesterol and metabolic indicators, (HR 0.085; 95% CI:0.007-0.16) using IMPACT therapy, and a pragmatic randomized controlled trial which reported that with the InShape intervention 51% of participants achieved clinically significant reduction in overall cardiovascular risk.Conclusion. Such a synthesis of findings provides valuable insights for future research, emphasizing the need for standardized outcome measures and more extended, comprehensive interventions.